Microstructure and elevated temperature wear behavior of HVOF-sprayed SS304L stainless-steel coating - Subbarao Medabalimi; Suresh Gudala; Uzwalkiran Rokkala; Ajit M. Hebbale; M. R. Ramesh (Discover Applied Sciences)
Abstract The paper aims to investigate the performance of the SS304L stainless steel coating on wear properties by varying load, temperature and velocity. Stainless-steel coatings were fabricated by high-velocity oxy-fuel spraying (HVOF) on superfer800. Surface morphology, elemental distribution and phase analysis were expressed by SEM, EDS, and XRD, respectively. The porosity, average surface roughness, and average microhardness of HVOF stainless steel coating are 2%, 7 µm, and 1167 ± 54 HV0.3, respectively. The wear rate of stainless-steel coating is 0.5 × 10−3 mm3/m at 600 °C with 20 N loads, which is about 16 times lower than the substrate. Adhesion and abrasion are the main wear mechanisms of HVOF stainless steel coatings during high-temperature tests. Comparing to superfer800 substrate, stainless steel coatings showed superior wear resistance at all the loads, temperature and velocities.